The Roles and Capabilities of Formal, Non-Formal, and Informal Institutions in Shaping Education Access in Cigugur Sub-district, West Java, Indonesia - Michelle Lim; Lucky Permana; Vinsensius Billy Hongo; Kanaya Kiandra; Kathryn Nabasa; Albert Hasudungan (Budapest International Research and Critics University, 2021)
The objective of this research paper is to explore the capacities of formal, non-formal, and informal educational institutions, as parts of social institutions. The roles of these institutions will be assessed within the urban, middle, and rural areas of Cigugur sub-district in Kuningan. This research uses qualitative methods, comprising interview and 1-month participant observation in the field. From this research, it was found that the education access in the urban areas of Cigugur boasts an abundance of formal education, in which the skills that were shaped are literacy and communication skills. On the other hand, the middle - areas, which lack formal education, rely on non-formal institutions (such as the local churches and local Islamic organizations (pesantren) to shape ethical and entrepreneurship education through a series of communal meetings. In fact, due to the rare availability of formal education in the rural areas, knowledge spillover from older to younger generations is delivered through informal conversations to shape basic entrepreneurial skills in their informal businesses. The academic contribution of this article is to illuminate the different roles and capabilities of social institutions to deliver different access to education in their various geographical contexts.